Usage and attitudes toward pornography among young adults in Iceland - Ingunn Eva Reynisdóttir 2000- (2023)
Nearly all Icelanders have been exposed to pornography in their lifetime and porn has become much more accessible. There is a lack of research on pornographic attitudes in Iceland. This study aimed to examine attitudes toward pornography among young adults in Iceland. Conveniently sampled participants were 151 in total, ranging in age from 18 to 30-years-old. The study was a quantitative research design; participants answered a questionnaire consisting of 23 questions. SPSS was used to analyze data. According to findings, women had a significantly more negative attitude toward pornography (p = .060), while men were close to having a significantly more positive attitude toward pornography (p = .002). No correlation was found between the age of first watching porn and attitude. Frequent porn usage was associated with more positive attitudes. People who watch porn for entertainment and masturbation had more positive attitudes, and people who watch porn for education had less negative attitudes. Participants that watched traditional pornography (“vanilla”), and kink porn, had significantly more positive attitudes toward pornography. In conclusion, the results indicate that attitudes toward pornography vary between genders and are influenced by personal experiences. Keywords: Pornography, attitudes, gender differences, usage Nær allir Íslendingar hafa horft á klám á lífsleið sinni og klám er orðið mun aðgengilegra. Það er skortur á rannsóknum á klámrænum viðhorfum á Íslandi. Markmið rannsóknarinnar var að kanna viðhorf ungs fólks á Íslandi til kláms. Þátttakendur voru alls 151, á aldrinum 18 til 30 ára í hentugleikaúrtaki. Rannsóknin var megindleg rannsóknaraðferð þar sem þátttakendur svöruðu spurningalista sem samanstóð af 23 spurningum. SPSS forritið var notað til að greina gögn. Niðurstöðurnar sýndu að konur höfðu marktækt neikvæðara viðhorf til kláms (p = .060), og karlar voru nálægt því að hafa marktækt jákvæðara viðhorf til kláms (p = .002). Engin fylgni fannst á milli aldurs þátttakenda að horfa fyrst á klám ...